Cytoprotective effect of kaempferol against palmitic acid-induced pancreatic β-cell death through modulation of autophagy via AMPK/mTOR signaling pathway. (15th June 2017) - Varshney, Ritu; Gupta, Sumeet; Roy, Partha
Abstract: Lipotoxicity of pancreatic β-cells is the pathological manifestation of obesity-linked type II diabetes. We intended to determine the cytoprotective effect of kaempferol on pancreatic β-cells undergoing apoptosis in palmitic acid (PA)-stressed condition. The data showed that kaempferol treatment increased cell viability and anti-apoptotic activity in PA-stressed RIN-5F cells and murine pancreatic islets. Furthermore, kaempferol's ability to instigate autophagy was illustrated by MDC-LysoTracker red staining and TEM analysis which corroborated well with the observed increase in LC3 puncta and LC3-II protein expressions along with the concomitant decline in p62 expression. Apart from this, the data showed that kaempferol up/down-regulates AMPK/mTOR phosphorylation respectively. Subsequently, upon inhibition of AMPK phosphorylation by AMPK inhibitors, kaempferol-mediated autophagy was abolished which further led to the decline in β-cell survival. Such observations collectively lead to the conclusion that, kaempferol exerts its cytoprotective role against lipotoxicity by activation of autophagy via AMPK/mTOR pathway. Highlights: Kaempferol exerts cytoprotective effect on palmitic acid-induced clonal pancreatic β-cells and isolated rat islets. Kaempferol-induced cytoprotective effect is mediated through induction of autophagy. AMPK/mTOR signaling pathway is involved in kaempferol-induced autophagy.